2020
DOI: 10.1038/s41598-020-62199-1
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic nitrogen fixation and endophytic bacterial community structure in Bt-transgenic chickpea (Cicer arietinum L)

Abstract: Symbiotic nitrogen fixation (SNF) of transgenic grain legumes might be influenced either by the site of transgene integration into the host genome or due to constitutive expression of transgenes and antibiotic-resistant marker genes. The present investigation confirmed proper nodulation of five tested Bt-chickpea events (IPCa2, IPCa4, IPCT3, IPCT10, and IPCT13) by native Mesorhizobium under field environment. Quantitative variations for nodulation traits among Bt-chickpea were determined and IPCT3 was found su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Although the other identified taxonomic groups have not been reported as part of the core microbial groups commonly found in wastewater communities, different studies have shown that these organisms have versatile metabolisms that can contribute to wastewater remediation. For instance, Sphingomonas and Shinella have been reported as genera involved in nitrogen fixation (Alok et al, 2020 ; Bizjak et al, 2023 ), phosphate fixation (Asaf et al, 2020 ; Jin et al, 2020 ; Liu et al, 2019 ), carbohydrate metabolism (Anderson & Wood, 1969 ), and photosynthesis (Kopejtka et al, 2021 ; Lu et al, 2022 ). Furthermore, while Pedobacter is a less studied genus, it has been associated with nitrogen fixation and phosphate fixation (Liang et al, 2022 ; Vannier et al, 2023 ); and Parachlorella and the bacterial genus Sphingopyxis are recognized for their ability to participate in photosynthesis (Kopejtka et al, 2021 ; Sharma et al, 2021 ; Vello et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the other identified taxonomic groups have not been reported as part of the core microbial groups commonly found in wastewater communities, different studies have shown that these organisms have versatile metabolisms that can contribute to wastewater remediation. For instance, Sphingomonas and Shinella have been reported as genera involved in nitrogen fixation (Alok et al, 2020 ; Bizjak et al, 2023 ), phosphate fixation (Asaf et al, 2020 ; Jin et al, 2020 ; Liu et al, 2019 ), carbohydrate metabolism (Anderson & Wood, 1969 ), and photosynthesis (Kopejtka et al, 2021 ; Lu et al, 2022 ). Furthermore, while Pedobacter is a less studied genus, it has been associated with nitrogen fixation and phosphate fixation (Liang et al, 2022 ; Vannier et al, 2023 ); and Parachlorella and the bacterial genus Sphingopyxis are recognized for their ability to participate in photosynthesis (Kopejtka et al, 2021 ; Sharma et al, 2021 ; Vello et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is consistent with those obtained by Dahalet al, (2017) who said that the abilities of some genera belonging to four phyla such as Actinomycetes, Bacteroidetes, Proteobacteria and Firmicutes can increase the activity of atmospheric nitrogen-fixing bacteria. Additionally, Alok et al (2020), found that the investigation of Bt-chickpea root and nodule endophytic bacterial community structure showed that in the four phyla detected, Actinobacteria accounted for 0.17% of the phyla Proteobacteria, Cyanobacteria, Firmicutes, and Actinobacteria. According to Abadi et al (2020) who found that the attendance rate of these four phyla is affected by the host plant.…”
Section: Nitrogenase Activity (N 2 -Ase)mentioning
confidence: 99%
“…The frequent application of microbial communities as bioinoculants for increased nutrient mobilization, stress resilience, and plant growth-promoting traits has been well documented (ALKahtani et al, 2020;Alok et al, 2020). Magallon-Servin et al ( 2020) designed a consortia of phosphate rock-solubilizing bacteria for testing their capacity in phosphate solubilization, biofilm formation, and root colonization.…”
Section: Microbe-based Manipulationsmentioning
confidence: 99%